2022
DOI: 10.1186/s10086-022-02058-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of microstructures within an annual ring of Douglas fir (Pseudotsuga menziesii) by dynamic mechanical analysis and small angle X-ray scattering

Abstract: Dynamic mechanical analysis (DMA) and small angle X-ray scattering (SAXS) measurements of water-saturated wood of Douglas fir (Pseudotsuga menziesii) in the temperature range of 0 ℃ to 100 ℃ were focused to clarify microstructural changes within an annual ring. The following results were obtained. Thermal softening behavior caused by micro-Brownian motion of lignin was observed in both earlywood and latewood. The peaks of tanδ were found at around 95 ℃ for earlywood and at around 90 ℃ for latewood. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…For softwoods, the peak temperature of tanδ of EW at 0.5 Hz appeared at higher temperatures than those of LW as in the previous report [8]. In addition, the peak temperature of tanδ of R specimens was similar to those of EW except for Pseudotsuga menziesii and Abies sachalinensis, for which the peak tanδ of R specimens was not observed.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…For softwoods, the peak temperature of tanδ of EW at 0.5 Hz appeared at higher temperatures than those of LW as in the previous report [8]. In addition, the peak temperature of tanδ of R specimens was similar to those of EW except for Pseudotsuga menziesii and Abies sachalinensis, for which the peak tanδ of R specimens was not observed.…”
Section: Resultssupporting
confidence: 76%
“…However, the relationship between lignin structure and thermal softening properties within an annual ring has not been investigated. Our previous studies have shown that EW and LW of Douglas fir (Pseudotsuga menziesii) have different thermal softening properties [8]. The peak of tanδ was found at around 95 °C for EW and around 90 °C for LW [8].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations